2020
DOI: 10.1200/go.20.00165
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Indocyanine Green Plus Methylene Blue Versus Radioisotope Plus Methylene Blue Dye Method for Sentinel Lymph Node Biopsy in Node-Negative Early Breast Cancer

Abstract: PURPOSE Sentinel lymph node biopsy (SLNB) by dual-dye method (radioisotope plus blue) is the gold standard for axillary staging in patients with breast cancer, but in developing countries, logistic issues and financial constraint play a vital role. Recently, indocyanine green (ICG) has emerged as an alternative to radioisotope (technetium-99 [Tc-99]) for SLNB in breast cancer. This study compared the diagnostic performance of Tc-99 plus methylene blue (MB) dye versus ICG + MB dye SLNB. METHODS Two hundred seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
2
25
2
1
Order By: Relevance
“…They received combined ICG-blue dye technique and SN localization was successful with ICG in all patients in this subgroup. This is in accordance with recent studies that show promising results of this tracer combination after neoadjuvant chemotherapy with an identification rate ranging from 83% to 100% (20)(21)(22) and very low false-negative rates (22).…”
Section: Discussionsupporting
confidence: 93%
“…They received combined ICG-blue dye technique and SN localization was successful with ICG in all patients in this subgroup. This is in accordance with recent studies that show promising results of this tracer combination after neoadjuvant chemotherapy with an identification rate ranging from 83% to 100% (20)(21)(22) and very low false-negative rates (22).…”
Section: Discussionsupporting
confidence: 93%
“…ICG dye SLNB is easy to use, of low cost and possible in a resource-constrained setting without nuclear medicine setup. With ICG, dual dye SLNB can be offered in all eligible patients without radioactive dye, which has given momentum to adopting this procedure in developing countries [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of using ICG for SLNB include a high detection rate, low cost, and simplicity of use [ 21 ]. Previous studies have reported that ICG is equivalent to the radioisotope for SLNB in patients with breast cancer [ 22 23 ]. However, the concordance between the order derived from the amount of radioisotope uptake and the intensity of ICG fluorescence during SLNB is yet to be studied.…”
Section: Discussionmentioning
confidence: 99%